Generation of Binary Trees in B-Order From (0-1) Sequences - Ahrabian, Hayadeh; Nowzari-Dalini, Abbas (Malaysian Journal of Computer Science, 2004)
An efficient recursive algorithm has been developed to generate binary trees in B-order from 0-1 sequences. The generation algorithm produces each tree in constant average time O(1). The ranking and unranking algorithms with O(n) time complexity are also presented.